Early years assessment : personal, social and emotional development - Fitzhenry, Trudi; Murphy, Karen (London : Bloomsbury, 2017)
Cover -- Title -- Copyright -- Contents -- Introduction -- How to use this book -- Chapter 1: 0 - 11 months -- Chapter 2: 8 - 20 months -- Chapter 3: 16 - 26 months -- Chapter 4: 22 - 36 months -- Chapter 5: 30 - 50 months -- Chapter 6: 40 - 60+ months -- Appendix -- Songs and rhymes -- Glossary -- Bibliography.
Keywords: Child development. -- Socialization. -- SOCIAL SCIENCE -- Discrimination & Race Relations